Persistent diarrhoea in Zairian AIDS patients: an endoscopic and histological study. Issue 12 (December 1988) - Colebunders, R; Lusakumuni, K; Nelson, A M; Gigase, P; Lebughe, I; van Marck, E; Kapita, B; Francis, H; Salaun, J J; Quinn, T C
Abstract : To determine the aetiology of persistent diarrhoea in African patients with acquired immunodeficiency syndrome (AIDS), 42 patients with human immunodeficiency virus (HIV) and persistent diarrhoea were enrolled in a microbiological, endoscopic, and histological study. Cryptosporidium was the intestinal parasite most often identified (30%); Isospora belli was found in 12% of the patients. Histological examination of the duodenal mucosa showed a non-specific inflammatory reaction in a significantly higher number of HIV-seropositive patients (82%) than HIV-seronegative controls without diarrhoea (52%) (p = 0.02). Lymphocytes were more likely to be found in inflammatory reactions in HIV-seropositive patients than in controls (p less than 0.0001). Pathogens were observed in histological sections of the duodenum of HIV-seropositive patients only (p = 0.002) and included cryptosporidia (four patients) Isospora belli (one), Strongyloides stercoralis (one), and Cryptococcus neoformans (one). On histological examination the rectal mucosa of HIV-seropositive patients and controls was similar, except eosinophils were more likely to be present in inflammatory reaction in HIV-seropositive patients (p = 0.05) and enteric pathogens were observed only in HIV-seropositive patients (cytomegalovirus inclusion bodies (one) and Schistosoma mansoni (two). The aetiology of persistent diarrhoea in most African AIDS patients remains unclear.